Perception of Direct and Indirect Compensations Fulfillment on Hazardous Work Environment - Chun-Hsi Vivian Chen; Setyabudi Indartono (Jurnal Ekonomi dan Pendidikan, 2008)
This paper investigates how ages, tenure, employees rank and work status related to perception of direct and indirect compensations fulfillment in a hazardous work environment. This study found that age, tenure, employees rank and work status are positively related to perception of direct and indirect compensations fulfillment. Implication for research and practice are discussed.